Quasifractal Networks as Current Collectors for Transparent Flexible Supercapacitors. (19th September 2019) - Chen, Shiqian; Shi, Bibo; He, Weidong; Wu, Xiayan; Zhang, Xian; Zhu, Yanbo; He, Shan; Peng, Haihui; Jiang, Yue; Gao, Xingsen; Fan, Zhen; Zhou, Guofu; et al.
Abstract: A high performance, transparent, and simultaneously mechanically flexible supercapacitor, with electrodes based on a bio‐inspired, quasifractal metallic network is demonstrated. Excellent performance parameters, such as the specific capacitance of 5.6 mF cm −2 (at 45% transparency), great long‐term electrochemical and mechanical stability under stress, and low cost, make this one of the best reported, and most promising candidates for applications in the wearable, transparent integrated electronics. Abstract : A transparent, flexible supercapacitor is assembled by sandwiching a gel electrolyte between two quasifractal Au leaf venation network electrodes, coated with polypyrrole. The supercapacitor areal capacitance of 5.6 mF cm −2, and 45% optical transparency rank among the best reported, and its superb stability and mechanical flexibilty promise successful application.